PROBLEMS IN PRODUCTION AND MARKETING OF POMEGRANATE (Punica granatum) â€“ A CASE OF AFGHANISTAN FARMERS - P. RADHIKA, SURGUL, SEEMA and (The Journal of Research, PJTSAU, 2019)
Pomegranate production is a significant contributor to the Afghans agricultural economy. Pomegranate is a major fruit crop in many provinces such as Kandahar, Helmand, Wardak, Ghazni, Paktia, Farah, Kapisa and Balkh, and is the source of the livelihood for thousands of people. Afghanistan is known as â€œThe country of the pomegranate fruitâ€ in view of not only its conventional methods of cultivation but also for the quality of the landraces grown. Some leading botanists believe that Afghanistan is the cradle of world pomegranate production. Afghanistan has more varieties of pomegranate trees than anywhere else in the world. Since 1970s, political turm oil and wars have ravaged the country; this had a serious effect on exporting the fruit to its biggest markets in Pakistan and India. (Sadiq, 2010)